2021
DOI: 10.3390/biomedicines10010002
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase-Induced Patellar Tendinopathy with Neovascularization: First Results towards a Piglet Model of Musculoskeletal Embolization

Abstract: Background: Therapeutic strategies targeting neovessels responsible for musculoskeletal chronic pain have emerged, including neovessels embolization. Our study aimed to develop a large animal model of patellar tendinopathy with neovascularization. Methods: Nine 3-month-old male piglets (18 patellar tendons) received percutaneous injections of increasing doses of collagenase (0 to 50 mg) at day 0 (D0). Tendinopathy was evaluated by ultrasound (D7 and D14). Neovascularization was evaluated visually and on angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Histological evaluation and semi-quantitative analysis revealed collagen ber disarray and extensive in ammatory cell in ltration in the AT group compared to the control group, indicating structural damage to the collagen bers (Fig 2D & Fig 4D).. To establish a reliable rabbit model of collagenase-induced tendonitis, we compared the degenerative potential of two different concentrations of type I collagenase and focused on gait analysis, macroscopic changes, and histopathology at different time points (15 days and 45 days) in rabbits. Our results align with other studies conducted in large animals, where the severity of pathology is related to the amount of injected collagenase [29][30] .…”
Section: Discussionsupporting
confidence: 92%
“…Histological evaluation and semi-quantitative analysis revealed collagen ber disarray and extensive in ammatory cell in ltration in the AT group compared to the control group, indicating structural damage to the collagen bers (Fig 2D & Fig 4D).. To establish a reliable rabbit model of collagenase-induced tendonitis, we compared the degenerative potential of two different concentrations of type I collagenase and focused on gait analysis, macroscopic changes, and histopathology at different time points (15 days and 45 days) in rabbits. Our results align with other studies conducted in large animals, where the severity of pathology is related to the amount of injected collagenase [29][30] .…”
Section: Discussionsupporting
confidence: 92%
“…Results of a recent study in a large animal, piglets, showed that ultrasound-guided injection of type 1 collagenase inside the patellar tendon allowed the generation of a tendinopathy model with neovessels in piglets. In addition, the piglets that successfully modeled the pigs showed better tolerance and no suffering sign (60). The significance of this study not only suggests the feasibility of large animals such as piglets in basic research, but also predicts the potential role of type 1 collagenase in the treatment of tendinopathy.…”
Section: From Basic Research To Clinical Administrationmentioning
confidence: 71%
“…Eight 3-month-old male piglets underwent percutaneous injection of collagenase type I (Sigma-Aldrich, St. Louis, MO, USA) under ultrasound guidance at a dose of 25 mg, according to the model and protocol previously published [16]. It was performed in accordance with the National Institute of Health guidelines for the use of laboratory animals.…”
Section: Patellar Tendinopathy Inductionmentioning
confidence: 99%
“…However, there are only a few large models of tendinopathy allowing angiographic exploration for embolization. A porcine model of patellar tendinopathy with neoangiogenesis was thus developed by our team [16]. A previous study showed the feasibility and reproducibility of induced patellar tendinopathy after collagenase injection.…”
Section: Introductionmentioning
confidence: 99%